2017
DOI: 10.1021/acs.biomac.6b01845
|View full text |Cite
|
Sign up to set email alerts
|

Carborane Derivative Conjugated with Gold Nanoclusters for Targeted Cancer Cell Imaging

Abstract: Polyhedral borane derivatives have been utilized in the treatment of boron neuron capture therapy (BNCT) for brain glioma, and much attention has been paid to search excellent biocompatible boron-rich composites for effective cancer BNCT therapy. In this study, we have exploited the self-assembly of the gold nanoclusters with carborane amino derivatives (GNCs-CB) for the precise bioimaging of cancer cells and targeted delivery of this carborane compound to the tumors. Our observations demonstrate that the GNCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Wang et al [106] reported the gold nanoclusters with carborane amino derivatives for the targeted delivery of the carborane compound to the tumors and precise bioimaging of cancer cells. They prepared carborane derivative (NH 2 NH 3 ) + [7-NH 2 (CH 2 ) 3 S-7,8-C 2 B 9 H 11 ]according to the literature [107], and stored it at -18 • C. Gold nanoclusters (GNCs) were freshly prepared and dispersed in PBS (pH 7.2).…”
Section: Gold Nanocluster/nanoparticles With Borane For Bnctmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [106] reported the gold nanoclusters with carborane amino derivatives for the targeted delivery of the carborane compound to the tumors and precise bioimaging of cancer cells. They prepared carborane derivative (NH 2 NH 3 ) + [7-NH 2 (CH 2 ) 3 S-7,8-C 2 B 9 H 11 ]according to the literature [107], and stored it at -18 • C. Gold nanoclusters (GNCs) were freshly prepared and dispersed in PBS (pH 7.2).…”
Section: Gold Nanocluster/nanoparticles With Borane For Bnctmentioning
confidence: 99%
“…Illustration of the bioimaging process for cancer cells using gold nanocluster with carborane derivative (reprint from Ref [106]…”
mentioning
confidence: 99%
“…Electrochemical properties of these nanocomposites were also investigated [81,82]. The potential applications of carborane-based Au-NPs is extremely broad since examination of ion transport across biological membranes [83] or cancer applications [84] were notably developed.…”
Section: Carborane Clustersmentioning
confidence: 99%
“…They are considered nano-building blocks due to their diameters (1.5 nm), and are easily functionalized by one or several organic groups [45]. In The potential applications of carborane-based Au-NPs is extremely broad since examination of ion transport across biological membranes [83] or cancer applications [84] were notably developed.…”
Section: Poss Clustersmentioning
confidence: 99%
“…This is a special large steric skeleton with a very strong hydrophobic structure. Therefore, improvement of the chemical structure can alter the stability, water solubility, and biological activity of compatibility and allow wider applications of carborane as a BNCT agent [ 6 9 ]. Boron neutron capture therapy (BNCT) was first proposed as a potential cancer therapy in 1936, based on the thermal neutron captured by 10 B atoms then produces a 4 He (α-particle) and a 7 Li ion [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%